1994
DOI: 10.1111/j.1365-2494.1994.tb01994.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrification inhibitor and acid addition to cattle slurry on nitrogen losses and herbage yields

Abstract: Cattle slurry was applied to grassland on two contrasting soils in autumn and spring between 1987 and 1990. Slurry was applied with or without the addition of acid, to lower the pH to 5-5, and, in autumn only, with or without a nitrification inhibitor. Ammonia volatilization, denitrification and apparent recovery of N by the cut herbage accounted for 61-86% of the ammonium nitrogen (NH4*-N) applied in slurry. Estimates from lysimeter experiments indicated that nitrate leaching from autumn application may have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 15 publications
2
15
1
Order By: Relevance
“…The results from this experiment clearly shows that DCD can reduce N 2 O emissions from slurry application, which is in agreement with Vallejo et al (2006), Pain et al (1994 and Merino et al (2002). The largest percentage reduction occurred on the poorly drained HB site which is likely to be a combination of higher N 2 O emissions and slower degradation of DCD at lower soil temperatures (Kelliher et al, 2008;Rajbanshi et al, 1992).…”
Section: Effects Of Dcdsupporting
confidence: 88%
“…The results from this experiment clearly shows that DCD can reduce N 2 O emissions from slurry application, which is in agreement with Vallejo et al (2006), Pain et al (1994 and Merino et al (2002). The largest percentage reduction occurred on the poorly drained HB site which is likely to be a combination of higher N 2 O emissions and slower degradation of DCD at lower soil temperatures (Kelliher et al, 2008;Rajbanshi et al, 1992).…”
Section: Effects Of Dcdsupporting
confidence: 88%
“…With field application acidification, decreases of NH 3 emissions in the range of 40e80% with pig slurry (Stevens et al, 1989;Biocover A/S, 2012;Nyord et al, 2013) and 15e80% with cattle slurry (Stevens et al, 1989;Frost et al, 1990;Bussink and Bruins, 1992;Stevens et al, 1992;Frost, 1994;Pain et al, 1994) can be achieved.…”
Section: Nitrogen Emissionsmentioning
confidence: 96%
“…At these values, less than 1% of the ammonium nitrogen was emitted to the air, compared to nonacidified slurry. Kai et al (2008) concluded that, when trying to minimize the N losses, slurry acidification is equivalent to or more Stevens et al, 1989;Frost et al, 1990;Bussink and Bruins, 1992;Stevens et al, 1992;Pain et al, 1994;Frost, 1994 Berg and Pazsiczki, 2006;Petersen et al, 2012 efficient than other solutions such as covering the slurry store with leca ® pebbles, straw, natural surface crust, or a PVC cover. As previously referred to, the efficiency of acidification with regard to reducing NH 3 emissions depends on parameters such as the additive, target pH, slurry type, and step in the slurry management chain (Ndegwa et al, 2008).…”
Section: Nitrogen Emissionsmentioning
confidence: 98%
“…The report by Di and Cameron (2004a) showed that at a soil temperature of 8°C, the half-life of DCD was 111-116 days; at a soil temperature of 20°C the half-life of DCD was 18-25 days, and the application of DCD did not have a significant effect on soil microbial biomass. Many studies have focused on the effects of DCD on increasing the efficiency of N fertilizers and manures in intensively grazed dairy pasture systems and crops fields (e.g., Pain et al 1994;Williamson et al 1998;Di and Cameron 2002b). However, little attention has been paid to the effects of DCD application on reducing NO 3 − leaching and N 2 O emissions in intensive vegetable production systems.…”
mentioning
confidence: 99%